Age of introduction to animal source foods and its association with child growth indices in low-income informal settlements of Nairobi, Kenya - Boncyk, M.; Miller, M.E.; Blake, C.E.; Prieto-Merino, D.; Bukachi, S.A.; Ngutu, M.; Lepine, A.; Kadiyala, S.; Domínguez Salas, Paula (2024)
Objectives: Animal-sourced foods (ASFs) contain essential nutrients for human growth, maintenance, and repair. This study quantifies the relationship between the age of ASF introduction and later child growth indices in low-income Kenya informal settlements.